Possibilities of altering arm and shoulder muscle activation in a static therapeutic climbing exercise through arm position, hand support and wall inclination. Issue 9 (21st October 2017) - Pühringer, Martin; Strutzenberger, Gerda; Leitl, Daniela; Holzner, Konrad; Schwameder, Hermann
Abstract: The aim of the study was to quantify the activation of arm and shoulder muscles during a static therapeutic climbing exercise and to investigate the possibility of altering the muscle activation through arm position (Jug, Undercling, Sidepull internal rotated, Sidepull external rotated), hand support (one-handed, double-handed) and wall inclination (0°, 12°). Electromyographic (EMG) activity of 14 healthy, climbing unexperienced males for the right m. biceps brachii (BB), m. serratus anterior (SA), m. upper, middle and lower trapezius (UT, MT, LT) showed mainly low to moderate EMG activation levels (BB: 4.1–40.1% maximum voluntary isometric contraction (MVIC), SA: 4.5–24.5% MVIC, UT: 1.3–28.0% MVIC, MT: 8.6–47.1% MVIC, LT: 3.8–47.3% MVIC). Significant differences occurred between the four arm positions for the UT and LT. The one-handed support revealed significant higher muscle activation than the double-handed support in every condition except for SA in Undercling arm position at 12° wall inclination. Increasing the wall inclination (from 0° to 12° overhang) led to a significant increase in muscle activation in nearly every exercise variation and muscle. These findings suggest that arm position, hand support and wall inclination are appropriate possibilities of altering muscle activation patterns in therapeutic climbing.